2003
DOI: 10.1111/j.1365-2370.2003.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease: investigation of proposed causal variants in the CTLA4 gene region

Abstract: Coeliac disease (CD) is an immune-mediated enteropathy triggered by gluten in genetically predisposed individuals. Patients with CD have an increased prevalence of other autoimmune disorders, including type 1 diabetes (T1D) and Graves' disease (GD). CD shares with these conditions certain HLA susceptibility alleles. A number of studies have also shown association of autoimmune diseases, including CD, with the CD28-cytotoxic T lymphocyte antigen 4 (CTLA4)-inducible costimulator (ICOS) region of chromosome 2q33,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Our analyses in celiac disease case-control and familial cohorts have a 50% power to detect the effect of a polymorphism, conferring an OR of 2.0 (assuming an allele frequency of 50%). In accordance with our findings, recent studies have observed no association [20,26] or borderline significance [27] between CTLA4/ CT60 polymorphisms and celiac disease predisposition. All these observations suggest that the chromosome 2q33 linked susceptibility in celiac disease might be attributed to another genetic marker.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Our analyses in celiac disease case-control and familial cohorts have a 50% power to detect the effect of a polymorphism, conferring an OR of 2.0 (assuming an allele frequency of 50%). In accordance with our findings, recent studies have observed no association [20,26] or borderline significance [27] between CTLA4/ CT60 polymorphisms and celiac disease predisposition. All these observations suggest that the chromosome 2q33 linked susceptibility in celiac disease might be attributed to another genetic marker.…”
Section: Discussionsupporting
confidence: 95%
“…Table 1 lists the allelic distribution of CTLA4/CT60 polymorphism in patients with IBD and controls. The allelic distribution in controls was similar to that obtained in other Caucasian populations [20,21]. Allele frequencies were in Hardy-Weinberg equilibrium in both the patient and control groups.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…89,90 Outside the HLA region, both CD and autoimmune thyroid disease are reported to be associated with the gene encoding cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4), a candidate gene for conferring susceptibility to thyroid autoimmunity. [91][92][93] More recently, a study showed that 10 of 14 patients with Hashimoto's thyroiditis had genotypes compatible with CD (three patients had DQ heterodimer A1*0501, B1*0201, four had DRB1*04 and one had A1*0101, B1*0501). Six of these 14 patients showed an increased density of γδ + T-cell receptor-bearing intra-epithelial lymphocytes and signs of mucosal T-cell activation, both typical of CD.…”
Section: Pathogenesis Of Co-existent Autoimmune Thyroid Disease and CDmentioning
confidence: 99%
“…The influence of genetic polymorphisms of these immunoregulatory molecules on immune responses, susceptibility to disease, and transplant outcome has gained increasing interest in recent years. Most association studies between autoimmune diseases and the 2q33 region have focused mainly on CTLA4 gene polymorphisms [3,4]. However, because CD28, CTLA4,and ICOS loci are in close proximity, possible linkage disequilibrium (LD) between the alleles of these genes should be taken into account.…”
Section: Introductionmentioning
confidence: 99%